CONTROL DE LA REPRODUCCIÓN EN CARNÍVOROS DE ZOOLÓGICO - Gobello, Cristina (2002)
Improved living conditions and reproduction techniques in captive animals have increased the longevity and fecundity rates, thus contraception has become very important in zoos. Reproduction control is needed to prevent crowding in the available space, inbreeding, and also to allow normal social interactions among groups of animals. Much of what is known of carnivores reproduction control has been studied in detail in the domestic dog and cat; howerer, due to some physiological differences (e.g. seasonality, ovulation characteristics), results from domestic dogs and cats should be taken with caution before applying in wild carnivores. The aim of this review is to briefly describe the main contraceptive methods available for carnivores.